NAVIGATING THE POST-PANDEMIC GREENWASHING WAVE IN ENVIRONMENTAL REPORTING: A SCOPING REVIEW ACROSS BUSINESS, MANAGEMENT AND ACCOUNTING FIELDS - Mai Farhana Mior Badrul Munir; Azrul Abdullah; Marjan Mohd Noor (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2025)
Recent years have seen a growing number of companies promoting their environmental sustainability efforts. However, these claims are often undermined by greenwashing activities that raised concerns about the reliability of their environmental reporting. Despite the growing number of studies on greenwashing, a comprehensive review that identify, summarize and critically evaluating its underlying drivers remains limited, particularly across the fields of business, management, and accounting. Addressing this gap, the present study aims to thoroughly reviewing trends in greenwashing research and examine the emerging factors driving these activities, especially in the post-pandemic context. Using a scoping review method, twenty articles from the Scopus database between 2018 to 2023 were analyzed based on specific inclusion criteria. The findings reveal the absence of universally accepted definition of greenwashing, reflecting its diverse interpretation across disciplines. Notably, there has been a surge in greenwashing-related publications, predominantly in Q1 and Q2 journals. Furthermore, corporate governance mechanisms have emerged as significant influence shaping greenwashing activities following the COVID-19 pandemic. By synthesizing current literature, this study provides valuable insights into the governance structures shaping the greenwashing activities. Additionally, this study outlines several significant research gaps, provides a foundation for future research and emphasize the need for more in-depth research to reduce greenwashing activities in environmental reporting.